Reasserting the Rural Development Agenda : Lessons Learned and Emerging Challenges in Asia - Fuwa, Nobuhiko; Balisacan, A. M. (Book collections on Project MUSE., 2007)
Presents a reinvigorated agenda on agricultural and rural development in Asia both for research and policy discussions in the coming decades.